Prospects of Implementation of Blockchain Technology into Aquaculture Sector of Ukraine - Iermakova, Olga; Sedikova, Iryna; Dashian, Artem (Dr. Viktor Koval, 2022)
Introduction. The development of fish farming in aquaculture in a sustainable way ensures the sustainability of fisheries, which is associated with local problems in each region. Ukraine’s fish production has been falling sharply over the last 30 years, and in 2021 the decline was more than 87 percent in comparison with 1990. In the Ukrainian aquaculture sector, there is a high degree of bureaucracy and risks of corruption, which need to be addressed in order to find a solution for the economy and businessmen. World reports show that Ukraine is among the world's leaders in illegal fishing. Thus, it is highly necessary to implement technologies for sector traceability and transparency, i.e., blockchain. Aim and tasks. The main aim of this article is to research the possible mechanism of implementation of the transparent and efficient system of using the aquatic bioresources of Ukraine. A secondary aim would be to actualize the information regarding the use of blockchain technology in the aquaculture sector. Results. This research shows that Ukraine’s aquacultural sector is going through a crisis, which is being induced by the high level of corruption and poaching. The digitization of the aquaculture supply chain powered by blockchain technology has been proposed. The role of blockchain technologies is revealed through functions such as evidence, tamper-proof, transparency, and decentralization. It was investigated the positive impact of blockchain technology on aquaculture business, such as reduction in bureaucracy, quality assurance, improvement in information exchange, low cost of transactions, improvement in audit performance, easy recall process, product origin verification, and low probability of fraudulent activity. It would greatly reduce the time needed to gather all the documentation essential for work and reporting. The blockchain implementation roadmap has been developed, including the following stages: concept, legislation compliance, limited prototype, final vision, further research and optimization. Conclusions. Blockchain technology fits Ukraine’s economic goals in the long term perspective, such as continued digitalization of the country. Due to the blockchain technology, products of aquaculture would not enter the market unless registered in the unified system. That will influence the reduction of "informal economy" in the sector and the increase of market mechanisms. It will also have a positive influence on food security for the population and economic security for the producers. It will be a precedent for a fully transparent and digitalized field of economy.